Dansk-engelsk medicinsk ordbog. Generering af fagsprogsordbog fra glosekartotek - Pilegaard, Morten (HERMES - Journal of Language and Communication in Business, 1988)
A status report on the transformation of an idiosyncratic word list into a special-purpose dictionary is given. Pending the inclusion of additional lemmas and a modification of entry design that challenges the current trend in special-purpose dictionaries, the work will result in the first Danish-English medical dictionary.